Zanidatamab, a novel bispecific antibody, for the treatment of locally advanced or metastatic HER2-expressing or HER2-amplified cancers: a phase 1, dose-escalation and expansion study. Issue 12 (December 2022) - Meric-Bernstam, Funda; Beeram, Muralidhar; Hamilton, Erika; Oh, Do-Youn; Hanna, Diana L; Kang, Yoon-Koo; Elimova, Elena; Chaves, Jorge; Goodwin, Rachel; Lee, Jeeyun; Nabell, Lisle; Rha, Sun Young; et al.
Summary: Background: HER2-targeted therapies have substantially improved outcomes for patients with HER2-positive breast and gastric or gastro-oesophageal junction cancers. Several other cancers exhibit HER2 expression or amplification, suggesting that HER2-targeted agents can have broader therapeutic impact. Zanidatamab is a humanised, bispecific monoclonal antibody directed against two non-overlapping domains of HER2. The aim of this study was to evaluate the safety and anti-tumour activity of zanidatamab across a range of solid tumours with HER2 expression or amplification. Methods: This first-in-human, multicentre, phase 1, dose-escalation and expansion trial included patients aged 18 years and older, with a life expectancy of at least 3 months, with an Eastern Cooperative Oncology Group performance status of 0 or 1, and locally advanced or metastatic, HER2-expressing or HER2 -amplified solid tumours of any kind who had received all available approved therapies. The primary objectives of part 1 were to identify the maximum tolerated dose, optimal biological dose, or recommended dose of zanidatamab; all patients were included in the primary analyses. Part 1 followed a 3 + 3 dose-escalation design, including different intravenous doses (from 5 mg/kg to 30 mg/kg) and intervals (every 1, 2, or 3 weeks). The primary objective of part 2 was to evaluate the safety and tolerability of zanidatamab monotherapy in solid tumours. This trial is registered with ClinicalTrials.gov (NCT02892123 ), and parts 1 and 2 of the trial are complete. Part 3 of the study evaluates the use of zanidatamab in combination with chemotherapy and is ongoing. Findings: Recruitment took place between Sept 1, 2016, and March 13, 2021. In Part 1 (n=46), no dose-limiting toxicities were detected and the maximum tolerated dose was not reached. The recommended dose for part 2 (n=22 for biliary tract cancer; n=28 for colorectal cancer; and n=36 for other HER2-expressing or HER2 -amplified cancers excluding breast or gastro-oesophageal cancers; total n=86) was 20 mg/kg every 2 weeks. The most frequent treatment-related adverse events in part 1 of the study were diarrhoea (24 [52%] of 46 patients; all grade 1–2) and infusion reactions (20 [43%] of 46 patients; all grade 1–2). The most frequent treatment-related adverse events in part 2 of the study were diarrhoea (37 [43%] of 86 patients; all grade 1–2 except for one patient) and infusion reactions (29 [34%] of 86 patients; all grade 1–2). A total of six grade 3 treatment-related adverse events were reported in four (3%) of 132 patients. In part 2, 31 (37%; 95% CI 27·0–48·7) of 83 evaluable patients had a confirmed objective response. There were no treatment-related deaths. Interpretation: These results support that HER2 is an actionable target in various cancer histologies, including biliary tract cancer and colorectal cancer. Evaluation of zanidatamab continues in ongoing studies. Funding: Zymeworks.